A novel soft theoretic AHP model for project management in multi-criteria decision making problem - Bakshi T.; Som T.; Sarkar B. (My University, 2025)
The present paper introduces a model of decision-making problem in multicriteria optimization domain for project management. The model is built by combining the fuzzy soft set theory and analytical hierarchical model. The later is the well-known method of ranking the alternatives for multicriteria decision-making problem. The ultimate project selection is the best of many decisions associated with project management.Herewe illustrate the hybrid method by means of an application of the new mathematical model of soft set theory. © Springer India 2015.